2018
DOI: 10.1177/0002716218818056
|View full text |Cite
|
Sign up to set email alerts
|

Turkey: The Slippery Slope from Reformist to Revolutionary Polarization and Democratic Breakdown

Abstract: Under the Justice and Development Party AKP and Recep Tayyip Erdoğan, Turkey has become one of the most polarized countries in the world, and has undergone a significant democratic breakdown. This article explains how polarization and democratic breakdown happened, arguing that it was based on the built-in, perverse dynamics of an “authoritarian spiral of polarizing-cum-transformative politics.” Furthermore, I identify ten causal mechanisms that have produced pernicious polarization and democratic erosion. Tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(54 citation statements)
references
References 56 publications
(81 reference statements)
1
52
0
1
Order By: Relevance
“…This suggests that, in Turkey, political winners’ high SWD is likely to be an extension of their support for the incumbent party rather than being the result of their evaluations of the performance of democratic institutions. This finding also supports the previous research indicating high levels of political polarization based on party identity in Turkey (Aydın-Düzgit and Balta, 2019; Somer, 2019). However, it is worrisome because political losers’ SWD is important for a democratic regime (Nadeau and Blais, 1993).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This suggests that, in Turkey, political winners’ high SWD is likely to be an extension of their support for the incumbent party rather than being the result of their evaluations of the performance of democratic institutions. This finding also supports the previous research indicating high levels of political polarization based on party identity in Turkey (Aydın-Düzgit and Balta, 2019; Somer, 2019). However, it is worrisome because political losers’ SWD is important for a democratic regime (Nadeau and Blais, 1993).…”
Section: Discussionsupporting
confidence: 92%
“…Polarization through political parties has increased considerably since the JDP came to power in 2002 (Yardımcı-Geyikçi, 2014), which resulted in significant differences between the winners and the losers, in terms of their social and political attitudes. During the 2014 and 2018 presidential elections and the 2017 referendum, the votes were divided into two mutually disagreeing blocs (Somer, 2019). Research also revealed significant differences between the winners and losers in Turkey, in terms of their views of state institutions (Örselli, 2016; Sahin and Akboga, 2019).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, after a coup attempt against him in July 2016 failed, Erdoğan assumed emergency powers and pushed through the parliament and popular vote a set of constitutional reforms that changed the country's once parliamentary regime into a hyperpresidential one. This process of autocratization was accompanied by intense political conflict along partisan lines and gave birth to the current partisan landscape (Somer, 2019).…”
Section: The Turkish Case: Partisanship In the Context Of Incumbent Tmentioning
confidence: 99%